“…Rejected by Everybody All Her Life…” Adverse Childhood Issues in Toni Morrison’s Novel God Help The Child (2015) - Lahtiva Rahmadaniah Putri; Leni Marlina (Universitas Negeri Padang, 2023)
The goal of this study is to examine the adverse childhood that the protagonist of Toni Morrison's book